2006
DOI: 10.1007/s10194-006-0323-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical involvement during the description of head pain

Abstract: Pain perception involves several cortical areas. Our purpose was to examine cortical activity in patients describing their cephalic pain with the MacGill Pain Questionnaire (MPQ). Two SPECT analyses were performed in pain-free periods in 10 patients with migraine (n=8) or myogenous facial pain (n=2). The MPQ was administered in the first session, while no task was to be performed during the second session. Differences were calculated using statistical parametric mapping (SPM99), also taking the MPQ pain rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Imaging studies in pain populations including fibromyalgia [40], rheumatoid arthritis [41], and peripheral neuropathic pain [42] have found variation in BP of endogenous opioid peptides. Some of the areas of relationships between BP and sleep in the current analyses are similar to those found altered in functional imaging studies of persistent pain conditions [43–48]. However, opioid receptor BP is reduced in many pain conditions.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Imaging studies in pain populations including fibromyalgia [40], rheumatoid arthritis [41], and peripheral neuropathic pain [42] have found variation in BP of endogenous opioid peptides. Some of the areas of relationships between BP and sleep in the current analyses are similar to those found altered in functional imaging studies of persistent pain conditions [43–48]. However, opioid receptor BP is reduced in many pain conditions.…”
Section: Discussionsupporting
confidence: 69%
“…peptides. Some of the areas of relationships between BP and sleep in the current analyses are similar to those found altered in functional imaging studies of persistent pain conditions [43][44][45][46][47][48]. However, opioid receptor BP is reduced in many pain conditions.…”
Section: Discussionsupporting
confidence: 65%
“…There is some evidence supporting a role of OFC in headache, but it is unlikely to be migraine specific. Increased activity in the OFC was reported in episodic migraine (outside of attacks) and acute myogenous facial pain patients (28). A PET study showed decreased glucose metabolism in OFC in episodic migraine patients who were efficiently treated with external trigeminal nerve stimulation (29).…”
Section: Discussionmentioning
confidence: 99%